CHARACTERIZATION OF LANDFILL LEACHATES IN TURKEY - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2011)
Landfilling and leachate treatment is one of the most serious issues in solid waste management. Treatment of landfill leachate is very difficult due to its high pollutant loads. In order to understand the landfill stabilization phases and determine the convenient treatment techniques, detailed and long term physical and chemical characterization of leachate is required. In the scope of this study, leachate samples taken from selected municipal solid waste landfill sites which have different ages and exhibit different climatic conditions. Leachate samples collected from different cities in Turkey namely Istanbul, Ankara, Antalya, Bursa, Gaziantep, Samsun and Trabzon landfills were characterized in order to investigate the effects of stabilization periods, climate and landfill exploitation on leachate quality. As a consequence, leachate pollutant concentrations were found to be extremely different in landfills despite their similar climatic conditions. Moreover, organic concentrations fluctuated during one year period. There was a correlation between the organic pollutant concentration, BOD5/ COD ratio and landfill age. Although high BOD5/ COD ratios and COD concentrations up to 71000 mg/L were observed in young landfills, lower COD concentrations about 5000 mg/L were obtained in the landfills which were being operated more than two years. Different climatic conditions in landfill sites provided to understand the effects of climate and seasonal changes on leachate properties. In dry seasons, pollutant concentrations were found to be higher than rainy seasons due to a lack of dilution as a result of precipitation. BUD/COD ratio which is the most distinctive parameter for the stabilization of leachate was observed to be higher than 0.5 for most leachate samples except Ankara.
Keywords: Solid waste landfill; leachate; characterization; Turkey; MUNICIPAL SOLID-WASTE; RECIRCULATION; SLUDGE